A New Variant of Emissive RNA Alphabets. Issue 13 (2nd February 2022) - Ludford, Paul T.; Yang, Shenghua; Bucardo, Marcela S.; Tor, Yitzhak
Abstract: A new fluorescent ribonucleoside alphabet ( mth N) consisting of pyrimidine and purine analogues, all derived from methylthieno[3, 4‐ d ]pyrimidine as the heterocyclic core, is described. Large bathochromic shifts and high microenvironmental susceptibility of their emission relative to previous alphabets derived from thieno[3, 4‐ d ]pyrimidine ( th N) and isothiazole[4, 3‐ d ]pyrimidine ( tz N) scaffolds are observed. Subjecting the purine analogues to adenosine deaminase, guanine deaminase and T7 RNA polymerase indicate that, while varying, all but one enzyme tolerate the corresponding mth N/ mth NTP substrates. The robust emission quantum yields, high photophysical responsiveness and enzymatic accommodation suggest that the mth N alphabet is a biophysically viable tool and can be used to probe the tolerance of nucleoside/tide‐processing enzymes to structural perturbations of their substrates. Abstract : The substrate scope of T7 RNA Polymerase and adenosine deaminase (ADA) are expanded by the introduction of a new ribonucleoside alphabet based on a methylthieno[3, 4‐ d ]pyrimidine core. The majority of the new analogues display significantly red shifted emission relative to the corresponding thieno[3, 4‐ d ]pyrimidine and isothiazolo[4, 3‐ d ]pyrimidine based analogues.